AuReTim: an inexpensive and extensible open-source auditory psychomotor vigilance test - Straßer, Torsten; Rothert, Inga; Heine, Thomas; Peters, Tobias (Frontiers in Sleep, 2023)
Within a large joint research project aiming for characterizing the nonvisual effects of light (NiviL), AuReTim, a low-cost and extensible open-source portable psychomotor vigilance test using auditory stimuli was developed, tailored for field testing. Currently, an unprepared simple reaction time and a go/no-go paradigm using acoustic stimuli are implemented. AuReTim is based on inexpensive hardware, e.g. its core is a Raspberry Pi leveraging a touch screen as input. Its software is developed in JavaTM using open-source libraries, therefore providing connectivity with other research setups, e.g. EEG, and easy extensibility with other stimulus paradigms. A simulation study proved the precise timing of AuReTim with limits of agreement between -1.86 and 1.67 ms. AuReTim combines the mobility of tablet-based psychomotor vigilance tests with the usability of conventional computer-based tests, which is especially helpful in field studies. AuReTim was successfully applied to study the effects of different lighting on alertness and proved to be a valuable tool for studies using the central nervous activation level as an outcome measure.